Respuesta :

question a

g(x) times [tex]\sqrt{x-5}=\sqrt{x^2-5}[/tex]
divide both sides by √(x-5)
[tex]g(x)=\frac{\sqrt{x^2-5}}{\sqrt{x-5}}[/tex]
[tex]g(x)=\frac{(\sqrt{x-5})(\sqrt{x^2-5})}{x-5}[/tex]
[tex]g(x)=\frac{\sqrt{x^3-5x^2-5x+25}}{x-5}[/tex]


question b
[tex]g(x) \space\ times \space\ 1+\frac{1}{x}=x[/tex]
divide both sides by 1+1/x
[tex]g(x)=\frac{x}{1+\frac{1}{x}}[/tex]
times by x/x
[tex]g(x)=\frac{x^2}{x+1}[/tex]


question c
[tex]\frac{1}{x} \space\ times \space\ f(x)=x[/tex]
times both sides by x
[tex]f(x)=x^2[/tex]


question d
the (f*g)(x) collumn seems to have a domain of only x is greater than or equal to 0?
so maybe we squared the whole thing, ya
wait
ah, ya
basically
[tex]|x|=(\sqrt{x})^2=(\sqrt{x})(\sqrt{x})[/tex]
so f(x)=√x


a. [tex]g(x)=\frac{\sqrt{x^3-5x^2-5x+25}}{x-5}[/tex]
b. [tex]g(x)=\frac{x^2}{x+1}[/tex]
c.[tex]f(x)=x^2[/tex]
d. [tex]f(x)=\sqrt{x}[/tex]
f   = f(x)
g = g(x)

so.. the first column has the g expression and the second column has the f expression and the third column has their product

a)

[tex]\bf \begin{array}{cccllll} &g(x)&f(x)&(f\cdot g)(x)\\ &------&------&------\\ a)&g&\sqrt{x-5}&\sqrt{x^2-5} \end{array}\implies gf=\sqrt{x^2-5} \\\\\\ g=\cfrac{\sqrt{x^2-5}}{f}}\implies\boxed{g=\cfrac{\sqrt{x^2-5}}{\sqrt{x-5}}}[/tex]

b)

[tex]\bf \begin{array}{cccllll} &g(x)&f(x)&(f\cdot g)(x)\\ &------&------&------\\ b)&g&1+\frac{1}{x}&x \end{array}\implies gf=x \\\\\\ g=\cfrac{x}{f}\implies g=\cfrac{x}{1+\frac{1}{x}}\implies g=\cfrac{x}{\frac{x+1}{x}}\implies g=\cfrac{\frac{x}{1}}{\frac{x+1}{x}} \\\\\\ g=\cfrac{x}{1}\cdot \cfrac{x}{x+1}\implies \boxed{g=\cfrac{x^2}{x+1}}[/tex]

c)

[tex]\bf \begin{array}{cccllll} &g(x)&f(x)&(f\cdot g)(x)\\ &------&------&------\\ c)&\frac{1}{x}&f&x \end{array}\implies gf=x \\\\\\ f=\cfrac{x}{g}\implies f=\cfrac{x}{\frac{1}{x}}\implies f=\cfrac{\frac{x}{1}}{\frac{1}{x}}\implies f=\cfrac{x}{1}\cdot \cfrac{x}{1}\implies \boxed{f=x^2}[/tex]

d)

[tex]\bf \begin{array}{cccllll} &g(x)&f(x)&(f\cdot g)(x)\\ &------&------&------\\ d)&\sqrt{x}&f&|x| \end{array}\implies gf=|x| \\\\\\ f=\cfrac{|x|}{g}\implies f=\cfrac{|x|}{\sqrt{x}}\implies f=\cfrac{\pm x}{\pm\sqrt{x}}\implies \boxed{f=\pm \cfrac{x}{\sqrt{x}}}[/tex]


not sure if you are expected to rationalize a) and d), but we could always rationalize the denominator though

a)

[tex]\bf \cfrac{\sqrt{x^2-5}}{\sqrt{x-5}}\cdot \cfrac{\sqrt{x-5}}{\sqrt{x-5}}\implies \cfrac{\sqrt{x^2-5}\cdot \sqrt{x-5}}{(\sqrt{x-5})^2}\implies \cfrac{\sqrt{(x^2-5)(x-5)}}{x-5} \\\\\\ \cfrac{\sqrt{x^3-5x^2-5x+25}}{x-5}[/tex]

d)    [tex]\bf \pm\cfrac{x}{\sqrt{x}}\cdot \cfrac{\sqrt{x}}{\sqrt{x}}\implies \pm \cfrac{x\sqrt{x}}{x}[/tex]
ACCESS MORE